ARSITEKTUR KEKUASAAN DAN TERITORIALITAS: ANALISIS PSIKOLOGI DESAIN PADA SAORAJA LAPINCENG DI BARRU, SULAWESI SELATAN - Muhammad Rusdin Jumurdin; Muhammad Uliah Shafar (Nusantara Hasana Journal, 2025)
The traditional architecture of the Bugis Saoraja (royal palace) normatively functions as a physical representation of social and political structure. However, the specific mechanisms of how the spatial design of the Saoraja—particularly in Lapinceng, Barru—is used to assert and manage power have not yet been thoroughly analyzed using the framework of environmental behavior theory. This descriptive qualitative research aims to analyze the architectural function of Saoraja Lapinceng as a power control program through the lens of Territoriality and Proxemics theory. Data was collected through spatial observation, semiotic analysis, and interviews. The research findings indicate that Saoraja Lapinceng is an environment intentionally programmed to assert hierarchy. Power control is manifested through Firm Spatial Zoning that serves as a gatekeeping mechanism to separate Primary and Secondary Territories, Differentiation of Elevation (Pattolo) which creates the king’s visual dominance (Proxemics), and Material Semiotics including Timpa’lajja and premium wood, which reinforce legitimacy through status symbolism. This study concludes that Bugis vernacular architecture is deliberately designed to regulate social behavior, making a significant contribution to enriching the discourse on environmental psychology, especially within the context of the Nusantara region.